Dampak Suku Bunga, Inflasi dan Nilai Tukar Terhadap Return Obligasi Korporasi di Perbankan Indonesia (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study evaluates how macroeconomic variables such as interest rates, inflation, and exchange rates affect the returns on corporate bonds issued by the banking sector in Indonesia. Corporate bonds are an attractive investment alternative, but their performance is highly influenced by fluctuations in national economic conditions. This study uses secondary data obtained from company financial reports, macroeconomic data, and bond market information over a certain period. Multiple linear regression analysis is applied to assess the extent to which each factor affects bond returns. The analysis results indicate that increases in interest rates and inflation tend to reduce bond returns, while the effect of exchange rates is inconsistent and depends on the economic stability at the time. These findings can serve as important considerations for investors, financial analysts, and policymakers in managing risks and opportunities in the Indonesia banking bondmarket.